Análisis comparativo del deterioro entre intersecciones y tramos en vías urbanas con pavimento asfáltico del Cantón Riobamba - Miller Arroba, José Enrique (2024)
The study presents a comparative analysis of the deterioration of flexible pavements at intersections and segments of asphalted urban roads in the Riobamba canton. The main objective is to evaluate and compare the pavement condition in both segments in order to determine whether there are significant differences in wear, through an exploratory and descriptive investigation using the Pavement Condition Index (PCI) and statistical techniques to analyze homogeneous and outlier data. The applied methodology involved dividing a 70 km sample of urban roads into 786 segments and 404 intersections, classified into two groups: roads with interventions in different years 0and roads with interventions in the same year. Through detailed field inspections, common failures such as cracks and deformations were identified, followed by the calculation of the PCI for each segment. The collected data were processed and analyzed using ARGIS and Microsoft Excel software. The results show that intersections tend to experience greater deterioration due to concentrated forces from braking and acceleration, and more intense traffic. On the other hand, segments show more uniform wear along their length. Additionally, roads with interventions in different years show greater uniformity in PCI, while roads intervened in the same year exhibit considerable variability between segments and intersections. This underscores the importance of periodic repaving to maintain pavement quality and uniformity.